Tren Penelitian Konseling Post-Modern: Kajian Bibliometrik dari Tahun 2020–2025 - Shidqah, Syafira Badhiatus; Rahmawati, Alya; Aji, Oetari Zakiyah (Lembaga Yasin AlSys, 2025)
This study aims to analyze the trends and characteristics of research on Solution-Focused Brief Therapy (SFBT) from 2020 to 2025 using a bibliometric and literature review approach. A total of 18 relevant articles were collected from the Google Scholar database and the Publish or Perish application, selected based on topic relevance, application context, and methodological completeness. The analysis focused on research methods, addressed issues, and the effectiveness of SFBT implementation. Bibliometric visualization using VOSviewer software identified three main thematic clusters interconnected by the central keyword